1999
DOI: 10.1073/pnas.96.20.11531
|View full text |Cite
|
Sign up to set email alerts
|

Soluble member(s) of the mesothelin/megakaryocyte potentiating factor family are detectable in sera from patients with ovarian carcinoma

Abstract: ABSTRACTmAb OV569 was made by immunizing mice with ovarian carcinoma cells. It binds to cells from ovarian carcinomas and, to a lesser extent, to cells from certain other carcinomas whereas the binding to normal tissues is low to nondetectable. It also binds to soluble molecule(s) in culture supernatants from antigen-positive carcinomas. OV569 recognizes a protein(s) of 42-45 kDa with the same N-terminal amino acid sequence as the membrane-bound portion of mesothelin and megakaryocyte potentiating factor (MPF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
271
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(286 citation statements)
references
References 20 publications
11
271
0
2
Order By: Relevance
“…Tumor cells are often identified by over-expressed surface markers [1,2], including particular receptors that respond to various signals and nutrients present in their surrounding environment. Unique surface markers include tumor cell-specific antigens that can be specifically targeted by monoclonal antibodies or ligand/receptor pair interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor cells are often identified by over-expressed surface markers [1,2], including particular receptors that respond to various signals and nutrients present in their surrounding environment. Unique surface markers include tumor cell-specific antigens that can be specifically targeted by monoclonal antibodies or ligand/receptor pair interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Current methods for detecting and separating cancer cells rely on observing morphological features or labeling with specific biomarkers. [1][2][3][4][5] Use of a biomarker is highly specific and accurate but requires laborious, time-consuming preparation for staining prior to separation, and a post process such as removal of labeling. Also, a limited number of effective biomarkers (e.g., aptamers 6 ) have been reported for cancer probing and diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Mesothelin has been found to be highly overexpressed in these intraperitoneal tumors. [11][12][13][14][15] Furthermore, it is absent or present in low levels in normal tissues and other types of cancer. 11 In addition, it has been suggested that mesothelin is a highly immunogenic protein in cancers with high mesothelin expression.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] Furthermore, it is absent or present in low levels in normal tissues and other types of cancer. 11 In addition, it has been suggested that mesothelin is a highly immunogenic protein in cancers with high mesothelin expression. For example, Ho et al 16 showed that a high percentage of antimesothelin antibodies was found in ovarian cancer and mesothelioma patient sera and was associated with high expression of the antigen in tumors.…”
Section: Introductionmentioning
confidence: 99%